Determination of Predictive Power of CRIB-II and SNAPPE-II in Mortality Risk of Neonates with Low Gestational Age or Birth Weight Admitted to the Neonatal Intensive Care Unit - Hossein Dalili; Nahid Farrokhzad; Zeinab Kavyani; Leyla Sahebi; Abbas Habibelahi; Mina Ashrafzadeh; Firuzeh Faridpur; Mamak Shariat (Mashhad University of Medical Sciences, 2020)
Background: Risk scoring systems evaluate neonatal outcomes using perinatal and neonatal status. The present study aimed to predict the mortality risk of preterm or low birth weight infants using the Clinical Risk Index for Babies (CRIB-II) and Score for Neonatal Acute Physiology Perinatal Extension (SNAPPE-II) scoring systems.Methods: This prospective cohort study investigated the preterm neonates admitted to the Neonatal Intensive Care Unit (NICU) of Vali-e-Asr Hospital, Tehran, Iran, with the birth weight of ˂1500g or a gestational age˂32weeks using the CRIB-II and SNAPPE-II scoring systems within the first 12 h after birth. The area under the curve, sensitivity, specificity, positive and negative predictive values of the scoring systems, as well as the association between neonate factors and neonatal death were calculated in this study.Results: Out of 344 neonates under study, 253casessurvived after24hof birth and 91 newborns died. The total CRIB-II scores in survived and deceased infants were 6.12 and 10.28, respectively. The area under the receiver operating characteristic (ROC) curve with a cut-off point of 8.5 was obtained at 0.838. Moreover, the sensitivity, specificity, positive predictive value, and negative predictive value were estimated at 74.4%, 78.65%, 55.37%, and 89.68%, respectively, for the CRIB-II system. Total scores of SNAPPE-II in survived and deceased infants were 16.9 and 51.6, respectively. The area under the ROC curve with a cut-off point of 27.5 was determined at 0.887. Sensitivity (84.44%) and specificity (79.05%) were calculated for the SNAPPE-II. Furthermore, positive and negative predictive values were 58.91% and 93.46%, respectively.Conclusion: This study demonstrated that the CRIB-II and SNAPPE-II scoring systems can be useful mortality predictors for at-risk neonates.